2016
DOI: 10.1590/1678-457x.0094
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the quality of oil extracted from two tucumã varieties using supercritical carbon dioxide

Abstract: The vast Amazon region has considerable territorial peculiarities and plant species diversity, sometimes from the same botanical family, which can exhibit significant differences in physicochemical properties. From this diversity, two species stand outAmazonas tucumã (Astrocaryum aculeatum Meyer) and Pará tucumã (Astrocaryum vulgare Mart.). The research focus is to analyze, comparatively, these oleaginous fruits, their similarities, particularities and potentials regarding the oil quality extracted from two tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 17 publications
0
26
1
2
Order By: Relevance
“…Comparing the outcome of this investigation with that of Serra et al [24], who evaluated the quality standards of buriti (Mauritia flexuosa) oil and pracaxi (Pentachletra Macroloba) oil, high values of acidity and peroxide were found, a few above those determined in this investigation and recommended in the legislation (5.76mg KOH g -1 and 12.05mEq kg -1 ; 5.44mg KOH g-1 and 8.23mEq kg -1 , respectively). In another survey, Santos et al [25], when assessing the Patauá (Oenocarpus bataua) oil, found averages of 1.40mg KOH g -1 and 9.64mEq kg -1 in the acidity and peroxide index respectively, and Costa et al [6], in their investigations with Tucumã (Astrocaryum vulgare, Mart. ), found acid averages between 6.5mg to 20.3mg KOH g -1 and peroxides between 11.8 and 13.8mEq kg -1 [6].…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Comparing the outcome of this investigation with that of Serra et al [24], who evaluated the quality standards of buriti (Mauritia flexuosa) oil and pracaxi (Pentachletra Macroloba) oil, high values of acidity and peroxide were found, a few above those determined in this investigation and recommended in the legislation (5.76mg KOH g -1 and 12.05mEq kg -1 ; 5.44mg KOH g-1 and 8.23mEq kg -1 , respectively). In another survey, Santos et al [25], when assessing the Patauá (Oenocarpus bataua) oil, found averages of 1.40mg KOH g -1 and 9.64mEq kg -1 in the acidity and peroxide index respectively, and Costa et al [6], in their investigations with Tucumã (Astrocaryum vulgare, Mart. ), found acid averages between 6.5mg to 20.3mg KOH g -1 and peroxides between 11.8 and 13.8mEq kg -1 [6].…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 98%
“…In another survey, Santos et al [25], when assessing the Patauá (Oenocarpus bataua) oil, found averages of 1.40mg KOH g -1 and 9.64mEq kg -1 in the acidity and peroxide index respectively, and Costa et al [6], in their investigations with Tucumã (Astrocaryum vulgare, Mart. ), found acid averages between 6.5mg to 20.3mg KOH g -1 and peroxides between 11.8 and 13.8mEq kg -1 [6]. Most of the oils used for comparison showed higher acidity and peroxide indexes than the pupunha oils evaluated in this investigation.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hu et al (2013) reported maximum extraction at 60-80 mesh size in combination with temperature (30 • C), pressure (343.5 MPa), and CO 2 flux (80 mL) for oil extraction from Cuminum cyminum seeds. During extraction of oils from two tucuma species (Amazon tucumã (AT) and Parátucumã (PT) fruits) it was observed that sometimes the material is not very accessible to the supercritical solvent thereby lowering yield [84].…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…Com os avanços no ramo da pesquisa, diversas formas de aplicação da tecnologia em produtos e subprodutos vêm sendo desenvolvidas visando o aproveitamento integral e a aplicação nutricional destes pela aplicação de tecnologias de conversão em matérias-primas aproveitáveis em análise de alimentos. (COSTA, et al, 2016;SANTOS et al, 2018;SANTOS et al, 2019).…”
Section: Pesquisas Aplicadas Aos Produtos E Subprodutos: Relação Com unclassified